2022
DOI: 10.3390/healthcare10071277
|View full text |Cite
|
Sign up to set email alerts
|

Association between Blood Vitamin D Levels and Regular Physical Activity in Korean Adolescents

Abstract: This study aimed to investigate the relationship between vitamin D levels and physical activity in adolescents using data from the Korea National Health and Nutrition Survey (KNHANES). The serum vitamin D concentrations were measured between 2008 and 2014 and analyzed. Adolescents aged 13 to 18 years comprised 4527 of the 61,370 participants surveyed. A final dataset including 2811 adolescents was obtained after those with missing data were excluded. Those who did not participate or only participated in 1–3 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A previous study revealed that physical activity increases vit D, blood calcium, and bone mass and decreases calcium excretion [13]. In contrast, another study reported that less than 30 minutes of outdoor activity per day increases the risk of vit D de ciency by 1.32-fold [14]. Regularly engaging in physical activity has multiple bene ts for humans but is affected by environmental, socioeconomic, physiological, and psychological factors that can be stimulating or inhibiting [15].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed that physical activity increases vit D, blood calcium, and bone mass and decreases calcium excretion [13]. In contrast, another study reported that less than 30 minutes of outdoor activity per day increases the risk of vit D de ciency by 1.32-fold [14]. Regularly engaging in physical activity has multiple bene ts for humans but is affected by environmental, socioeconomic, physiological, and psychological factors that can be stimulating or inhibiting [15].…”
Section: Introductionmentioning
confidence: 99%